A Novel Silver Bioactive Glass Elicits Antimicrobial Efficacy Against Pseudomonas aeruginosa and Staphylococcus aureus in an ex Vivo Skin Wound Biofilm Model - Wilkinson, Holly N.; Iveson, Sammi; Catherall, Paul; Hardman, Matthew J. (Frontiers in Microbiology, 2018)
Biofilm infection is now understood to be a potent contributor to the recalcitrant nature of chronic wounds. Bacterial biofilms evade the host immune response and show increased resistance to antibiotics. Along with improvements in antibiotic stewardship, effective new anti-biofilm therapies are urgently needed for effective wound management. Previous studies have shown that bioactive glass (BG) is able to promote healing with moderate bactericidal activity. Here we tested the antimicrobial efficacy of a novel BG incorporating silver (BgAg), against both planktonic and biofilm forms of the wound-relevant bacteria Pseudomonas aeruginosa and Staphylococcus aureus. BgAg was stable, long lasting and potently effective against planktonic bacteria in time-kill assays (6-log reduction in bacterial viability within 2 hours) and in agar diffusion assays. BgAg reduced bacterial load in a physiologically relevant ex vivo porcine wound biofilm model; P. aeruginosa (2-log reduction) and S. aureus (3-log reduction). BgAg also conferred strong effects against P. aeruginosa biofilm virulence, reducing both protease activity and virulence gene expression. Co-culture biofilms appeared more resistant to BgAg, where a selective reduction in S. aureus was observed. Finally, BgAg was shown to benefit the host response to biofilm infection, directly reducing host tissue cell death. Taken together, the findings provide evidence that BgAg elicits potent antimicrobial effects against planktonic and single-species biofilms, with beneficial effects on the host tissue response. Further investigations are required to elucidate the specific consequences of BG administration on polymicrobial biofilms, and further explore the effects on host-microbe interactions.